Worldwide Prevalence of Poor Sleep Quality in Older Adults: A Systematic Review and Meta-Analysis - Parisa Kavousi; Ehsan Mali; Nasim Seifhashemi; Mohamad Souri; Leyla Pakravan; Fatemeh Khalili (Iranian Journal of Psychiatry)
Objective: The objective of this meta-analysis was to establish the prevalence of poor sleep quality among individuals aged over 60 years old, utilizing the Pittsburgh Sleep Quality Index (PSQI). Method: To identify appropriate records, a thorough search of PubMed, Scopus, and Web of Knowledge databases was conducted until May 22, 2024. The quality of the included studies was assessed using the Hoy tool. To calculate the pooled prevalence with a 95% confidence interval, the random effects model was utilized. Additionally, subgroup analyses were carried out to investigate the potential sources of heterogeneity. Results: This study examined 52 cross-sectional studies encompassing 24,217 individuals aged 60 and older. The quality of the studies was assessed, with 4 rated as moderate and 48 as good. China reported the lowest prevalence of poor sleep quality at 14%, while Malaysia recorded the highest at 96%. The overall pooled prevalence was found to be 50% (95% CI: 45-55%), exhibiting significant heterogeneity across the studies (I² = 99.60%, Pheterogeneity < 0.001). Subgroup analysis indicated that geographic location significantly influenced this heterogeneity (p < 0.001), with Africa showing a lower prevalence of poor sleep quality at 27% (95% CI: 23%-32%) compared to other regions. However, no significant differences were observed in the impact of other factors, such as gender, level of development, sample size, survey time, PSQI cut-off, and response rate on the overall heterogeneity of the analyzed data. Conclusion: This study reveals that approximately half of older adults experience poor sleep quality. However, this prevalence varies across different locations, underscoring the necessity for targeted interventions that consider regional factors influencing sleep health.